2018
DOI: 10.1093/ajcn/nqy158
|View full text |Cite|
|
Sign up to set email alerts
|

Validation of rapid 4-component body composition assessment with the use of dual-energy X-ray absorptiometry and bioelectrical impedance analysis

Abstract: Abstract Background The 4-component (4C) model is a criterion method for human body composition that separates the body into fat, water, mineral, and protein, but requires 4 measurements with significant cost and time requirements that preclude wide clinical use. A simplified model integrating only 2 measurements—dual-energy X-ray absorptiometry (DXA) and bioelectrical impedance analysis (BIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 16 publications
0
46
0
4
Order By: Relevance
“…The sample size is on the small end for repeatability and validity research, and an uneven number of male/female participants may have limited the ability to detect sex*assessment differences. Recent work has included smaller (Ng et al ., ), and 2–4 times larger (Nickerson et al ., ; Smith‐Ryan et al ., ; Bailey et al ., ) sample sizes. Finally, the age range of the present study was rather narrow.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The sample size is on the small end for repeatability and validity research, and an uneven number of male/female participants may have limited the ability to detect sex*assessment differences. Recent work has included smaller (Ng et al ., ), and 2–4 times larger (Nickerson et al ., ; Smith‐Ryan et al ., ; Bailey et al ., ) sample sizes. Finally, the age range of the present study was rather narrow.…”
Section: Discussionmentioning
confidence: 99%
“…The latter study found a mean difference of 0Á9% BF. A newly published study by Ng and colleagues also evaluated the 4C DXA for validity against isotopic dilution and 4C BP (Ng et al, 2018) . The root mean square after removing outliers from this study was 0Á8% body fat (Ng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations